1979
DOI: 10.1149/1.2128939
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Mass Transport Properties of  “ LiAl ”

Abstract: The compositional variations of the thermodynamic and mass transport properties of the ~ phase "LiAr' in the lithium-aluminum system have been investigated over the temperature range from 415 ~ to 600~ At 415~ the emf of the single phase "LiAI" lies between 300 and 70 mV relative to pure Li and this corresponds to a 'Li activity increasing from 0.0063 to 0.31 over the phase stability range from 46.8 to 55.0 atomic percent Li. At the ideal stoichiometry, the standard Gibbs free energy of formation of "LiAI" is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
527
0
2

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 829 publications
(552 citation statements)
references
References 16 publications
16
527
0
2
Order By: Relevance
“…It means that the calibration C d vs Re is developed by expressing this relation by polynomial Eq. [2]. It was done for pure aluminum because of known three determined physical properties.…”
Section: A Draining Crucible Methods (Dc): Density Surface Tension mentioning
confidence: 99%
See 1 more Smart Citation
“…It means that the calibration C d vs Re is developed by expressing this relation by polynomial Eq. [2]. It was done for pure aluminum because of known three determined physical properties.…”
Section: A Draining Crucible Methods (Dc): Density Surface Tension mentioning
confidence: 99%
“…[1] The attention has been paid for an even longer time to the use of lithium alloys as an alternative to elemental lithium. Especially interesting are the batteries working with molten salt electrolytes that operate above the melting point of lithium, the lithium-aluminum alloys, [2] for example. Apart from these, metallic systems: Li-Zn, Li-Sn, Li-Pb, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent work 4 has shown that the chemical diffusion coefficient of lithium in S-LiAl at the a + S phase boundary is extraordinarily large, about 10~4 cm 2 /sec. These facts make it reasonable to suggest that Li-Al electrode agglomeration may involve sintering by processes of vacancy diffusion.…”
Section: *Undergraduate Research Participant Eastern Illinois Univermentioning
confidence: 99%
“…Efforts to measure E 1 were unsuccessful and E 4 and E 5 could not be measured because these transitions do not occur under equilibrium conditions in LiCl-KCl eutectic electrolyte.…”
Section: Fes Electrode Studiesmentioning
confidence: 99%
“…Electro-analytical methods such as galvanostatic intermittent titration technique (GITT), potentiostatic intermittent titration technique (PITT) and electrochemical impedance spectroscopy (EIS) were used to understand the ion transport. 7,8 The diffusion coefficient obtained by these methods was useful to understand the ion transport process.…”
Section: Introductionmentioning
confidence: 99%